2021
DOI: 10.3390/ijms222312676
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ABA Signal Pathway Mediated by GABA Improves the Drought Resistance of Apple Seedlings

Abstract: Drought seriously affects the yield and quality of apples. γ-aminobutyric acid (GABA) plays an important role in the responses of plants to various stresses. However, the role and possible mechanism of GABA in the drought response of apple seedlings remain unknown. To explore the effect of GABA on apple seedlings under drought stress, seedlings of Malus hupehensis were treated with seven concentrations of GABA, and the response of seedlings under 15-day drought stress was observed. The results showed that 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Exogenous GABA reduces ethylene synthesis in the roots of Caragana intermedia to adapt to salt stress (Shi et al, 2010 ). Our previous studies found that exogenous GABA in apple improved the resistance of apple to drought, alkaline and cadmium stress as well as Marssonina apple blotch (Li, Liu, Peng, et al, 2020 ; Li, Li, et al, 2022 ; Liu et al, 2021 , 2022 ). Herein, we found that the content of GABA increased significantly after inoculation with C. fructicola (Figure S1 ), and we observed the effects of exogenous GABA application on reducing apple GLS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exogenous GABA reduces ethylene synthesis in the roots of Caragana intermedia to adapt to salt stress (Shi et al, 2010 ). Our previous studies found that exogenous GABA in apple improved the resistance of apple to drought, alkaline and cadmium stress as well as Marssonina apple blotch (Li, Liu, Peng, et al, 2020 ; Li, Li, et al, 2022 ; Liu et al, 2021 , 2022 ). Herein, we found that the content of GABA increased significantly after inoculation with C. fructicola (Figure S1 ), and we observed the effects of exogenous GABA application on reducing apple GLS.…”
Section: Discussionmentioning
confidence: 96%
“…The signalling molecule GABA plays an important role in plant biotic and abiotic stresses by hormone regulation, organic acid metabolism, ion absorption and transport, photosynthesis system, antioxidant system, and phenolic metabolism (Li, Liu, Sun, et al, 2020 ; Ramesh et al, 2015 , 2017 ; Xu et al, 2021 ). For example, the application of exogenous GABA can improve the drought resistance of apple seedlings through the abscisic acid signalling pathway (Liu et al, 2021 ). The GABA‐regulated glutathione pathway and antioxidant enzymes are involved in chlorothalonil‐induced pesticide detoxification in plants (Shan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ABA was not included in the metabolite profile in this study, we instead found increased levels of the signaling molecule GABA in both local and systemic leaves of co-infected plants. GABA is involved in the regulation of various pathways promoting tolerance to stresses and it affects stomatal closure by enhancing ABA production [ 69 , 70 , 71 , 72 ]. While stomatal closure improves drought tolerance and ABA has been shown to improve plant defenses against another potyvirus, plum pox virus [ 73 ], prolonged closure of stomata eventually has a negative impact on plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids play frequent roles in plant protection in the form of phytohormones, particularly as diterpene gibberellins, triterpene brassinosteroids (BRs), and sesquiterpene abscisic acid (ABA) (Patra et al, 2013;Chen et al, 2021a;Liu et al, 2021a). In lettuce, long-term high temperature expose facilitates the accumulation of gibberellin to accelerate bolting (Liu et al, 2020).…”
Section: Effects Of Environmental Factors On Terpenoid Biosynthesismentioning
confidence: 99%